USING VISUAL SCAFFOLDING STRATEGY FOR TEACHING READING IN JUNIOR HIGH SCHOOL - Lestari, Nurul Fauziyah; ., Misdi (ELT Perspective Jurnal Pendidikan Bahasa Inggris, 2016)
Abstract This research was aimed to investigate the effectiveness of using visual scaffolding strategy in teaching reading comprehension at the eighth grade of junior high school. The design of this study was a quasi experimental study. The subjects were the students of state junior high schools in Cirebon, Indonesia. The data were obtained by administering reading test and from observation as a supporting data analysis. The data of the test were analyzed by using t-test formula to know the difference of the studentsâ comprehension in reading narrative text between two groups. Meanwhile the result of the observation was analyzed descriptively. The results indicate that there was a significant difference on studentsâ learning result before and after Visual Scaffolding applied. Keywords: reading comprehension, narrative text, visual scaffolding strategy